Efektivitas Penggunaan Aplikasi Games Edukasi Sistem Tata Surya Berbasis Android Terhadap Minat Belajar Peserta Didik Kelas VI SDN Wonolopo 02 - Febriani, Dwi; Hidayati, Yeni Tri; Hidayatullah, Muchamad; Rani, Amanda Dwi Setyo; Aisyah, Diana Shafa Nur; Sutikno, Putri Yanuarita (Jurnal Ilmiah Wahana Pendidikan, 2025)
This study aims to determine the effectiveness of the use of Android-based educational game media on students' interest in learning solar system material in the subject of Natural and Social Sciences (IPAS) grade VI at SDN Wonolopo 02, Semarang City. This study uses a quantitative approach with a quasi-experimental method and a one-group pretest-posttest design. The sample in this study amounted to 28 students who were selected using purposive sampling techniques. The instrument used is a learning interest questionnaire with a Likert scale that has been tested for validity and reliability. Data were analyzed using a paired sample t-test with the help of SPSS version 26.0. The results of the study showed that there was a significant increase in students' interest in learning after using educational game media. This is shown by the tcal value of 50,857 > ttable 1.70562 with a significance value of 0.000 < 0.05. These findings reinforce that the use of Android-based educational games can be an innovative solution in creating more interactive, interesting, and fun learning, as well as effective in increasing students' interest in learning abstract materials such as the solar system